(untitled) (Fiep Bulletin - online, 2014)
The goal of the present work was to study the hepatic function of animals in a process of nutritional recovery associated or not with physical exercise (swimming 30 minutes/day during 8 weeks). Fifty two female Fisher rats were divided into six groups: Control Sedentary (CS), Control Trained (CT), Recovered Sedentary (RS), Recovered Trained (RT), Malnourished Sedentary (MS) and Malnourished Trained (MT). We have concluded that the protocol of nutritional recovery was efficient in promoting the recovery of body weight of the animals RS but exercise did not change this picture. Considering the activities of aminotransferases, alkaline phosphatase and the concentration of globulins, data suggest hepatic injure in the malnourished animals, and this has not occurred with recovered ones.